Regional Fibroblast Heterogeneity in the Lung: Implications for Remodeling - Kotaru, Chakradhar; Schoonover, Kathryn J; Trudeau, John B; Huynh, Mai-Lan; Zhou, XiuXia; Hu, Haizhen; Wenzel, Sally E (American journal of respiratory and critical care medicine, 2006)
Excessive deposition of extracellular matrix occurs in proximal airways of individuals with asthma, but fibrosis in distal lung has not been observed. Whether differing fibrotic capacities of fibroblasts from these two regions contribute to this variability is unknown. We compared morphologic and functional characteristics of fibroblasts isolated from proximal airways and distal lung parenchyma to determine phenotypic differences. Concurrent proximal airway and distal lung biopsies were obtained by bronchoscopy from subjects with asthma to isolate airway and distal lung fibroblasts, respectively. The following characteristics were compared: morphology, proliferation, alpha-smooth muscle actin expression, and synthesis of procollagen type I and eotaxin-1. Airway fibroblasts (AFs) are morphologically distinct from distal lung fibroblasts (DLFs): they are larger (2.3-fold greater surface area vs. matched DLFs; p = 0.02), stellate in appearance, and with more cytoplasmic projections compared with the spindle-shaped DLFs. AFs synthesized more procollagen type I than did DLFs at baseline (twofold higher; p = 0.003) and after transforming growth factor-beta stimulation (1.4-fold higher; p = 0.02). Similarly, AFs produced more eotaxin-1 than did DLFs at baseline (2.5-fold higher; p = 0.004) and after interleukin-13 stimulation (13-fold higher; p = 0.0001). In contrast, DLFs proliferate more than AFs with serum stimulation (about sixfold greater; p = 0.03). Unstimulated DLFs also expressed more alpha-smooth muscle actin than did corresponding AFs (p = 0.006). These studies suggest that at least two phenotypes of fibroblast exist in the lung. These phenotypic differences may partially explain the variable responses to injury and repair between proximal airways and distal lung/parenchyma in asthma and other respiratory diseases.